Cardiovascular disease prevention – point of view family doctor - Starczewska, Marta E.; Pietrasik, Arkadiusz; Główczyńska, Renata; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
In this article is presented analysis of data from doctor’s questionnaires which were sended to the family doctor’s in the course of POLKARD-SPOK national survey. This trial is performed as the part of National Programme of Prophylaxis and Treatment Cardiovascular Disease POLKARD 2003-2005. POLKARD-SPOK is the epidemiologic national survey aimed to estimate current condition of cardiology care practice among family doctors. Two types of questionnaires were performed; one concern doctors and the other concern patients. Analysis of the data from doctor’s questionnaire is the issue of this article.